Molecular alignments of σ phase in co-evaporated pentacene and perfluoropentacne film on SiO2 studied by grazing-incidence X-ray diffraction. (2nd September 2017) - Hirosawa, Ichiro; Watanabe, Takeshi; Koganesawa, Tomoyuki; Tada, Keisuke; Yoshimoto, Noriyuki
ABSTRACT: Grazing-incidence X-ray diffraction experiment suggested that σ-phase of pentacene and perfluoropentacene co-evaporated film was composed of polymorphs. Two ordered alloy and one random alloy alignments were found. Tilt angles of pentacene and perfluoropentacene were 20° and 21° in one ordered alloy alignment. The other ordered alloy alignment and random alloy alignment resembles to each other. Tilt angles of pentacene and perfluoropentacene was between 5° and 14°. Tilt angles of pentacnene and perfluoropentacene in amorphous phase were also estimated to be 20°.